Bioinspired self-adhesive polymer for surface modification to improve antifouling property - Heo, Seong-beom; Jeon, Young-Sil; Kim, Young Jun; Kim, Soo Hyun; Kim, Ji-Heung (SPRINGER, 2013)
The catechol functional group of dopamine (3,4-dihydroxyphenethylamine) forms a strong coordinate bond with both inorganic and organic substrates in a wet environment. The nonfouling surfaces required for this process are typically prepared through the immobilization of poly(ethylene glycol), so-called, PEGylation. In this work, polyaspartamides containing adhesive catechol and methoxy PEG pendants were synthesized from polysuccinimide through successive aminolysis reactions. The adhesion and crosslinking of the polyaspartamide derivatives in pH-controlled aqueous media was successfully utilized to modify a glass surface using a simple immersion method. Contact angle, alpha-step profiler, SEM and EDS, XPS, and AFM were used to characterize and verify the surface coating. In addition, the biocompatibility and antifouling properties of the modified surface were elucidated with a cell viability test, and a protein adsorption experiment, respectively. This biocompatible polymer system has biomedical application potential for use in adhesives and the surface coating of various biomaterials.
Keywords: PROTEIN ADSORPTION; POLYETHYLENE-GLYCOL; CROSS-LINKING; AMPHIPHILIC POLYASPARTAMIDES; BACTERIAL ADHESION; MYTILUS-EDULIS; CHAIN-LENGTH; DERIVATIVES; RESISTANCE; OXIDE